Lost in translation: What do Engel curves tell us about the cost of living? - Ingvild Almas; Timothy K. M. Beatty; Thomas F. Crossley (Institute for Fiscal Studies (IFS), 2018)
The Hamilton method for estimating CPI bias is simple, intuitive, and has been widely adopted. We show that the method conflates CPI bias with variation in cost-of-living across income levels. Assuming a single price index across the income distribution is inconsistent with the downward sloping Engel curves that are necessary to implement the method. We develop and implement the Translated Engel curve (TEC) method that disentangles genuine CPI bias from differences caused by comparing changes in the cost of living across different income levels - non-homotheticity. The TEC method gives substantially different estimates of CPI bias prior to major reforms to the CPI in 1999 (post-Boskin), but both methods suggest very little CPI bias thereafter.
Keywords: 330